Immediate effects of osteopathic treatment versus therapeutic exercise on patients with chronic cervical pain (2018)
Context. Alternatives to medication for immediate pain relief are needed because long-term use of pain medication has been associated with adverse effects. High-velocity, low-amplitude (HVLA) manipulation techniques (MTs) and craniocervical flexion (CCF) exercises have been frequently used in the management of chronic cervical pain. Objective. The study intended to compare the immediate effects on pain of a treatment using HVLA manipulation versus one using a CCF exercise protocol. Design. The research team designed a single-blinded, randomized clinical trial. Setting. The study was conducted at osteopathic clinics. Participants. Participants were 25 volunteer patients with chronic neck pain. Intervention. Participants were randomly enrolled in one of 2 groups: the HVLA manipulation group (MT group), n = 12, or the CCF exercise protocol group (CCF group), n = 13. Participants in the CCF group performed the exercise for 10 repetitions of a 10-s duration, with a 10-s rest interval between each contraction, for a total contraction time of 100 s and a total time of the session of 190 s. Outcome Measures • The outcomes were measured at baseline and at 60 s postintervention. The measures included (1) a visual analogue scale (VAS) completed during range of motion (ROM) measurement, (2) an evaluation of the ROM of the cervical spine, (3) a test of pressure pain thresholds (PPTs), and (4) electromyographic (EMG) activation of sternocleidomastoid muscle during a craniocervical flexion test. Results • Following both interventions, significant changes were found between baseline and immediately postintervention in the VAS score during ROM measurement for both groups, with P =.004 and P =.015, respectively. In the MT group, the measures for flexion (P =.001), right-side bending (P =.002), and left rotation (P =.005) changed significantly between baseline and postintervention; however, only flexion (P =.026) and extension (P =.040) ROM changed significantly between baseline and postintervention in the CCF group. Significant changes were observed in upper trapezius PPT following both interventions—MT group, P =.043, and CCF group, P =.005. In addition, significant changes in C5 PPT had occurred in the CCR group (P =.020). Between-group differences were significant for extension and right-side-bending ROM, with P =.019 and P =.012, respectively, and the changes between baseline and postintervention were greater in the MT group. None of the interventions led to changes in EMG. Conclusions • Although both interventions were associated with immediately improved ROM and pain after treatment, HVLA manipulation was more effective than CCF exercise in improving ROM and VAS during ROM. None of the interventions led to changes in EMG. © 2018, InnoVision Communications. All rights reserved.